0555 Absence Of Upper Airway Stimulation Surgical Learning Curve Effect On AHI And ESS Outcomes - Results From The Adhere Registry. (12th April 2019) - Strohl, Kingman; Schell, Amy; Heiser, Clemens; Waters, Tina; Steffen, Armin; Maurer, Joachim; Strollo, Patrick J; Soose, Ryan; Doghramji, Karl; Schwab, Richard; Withrow, Kirk
Abstract: Introduction: Upper Airway Stimulation (UAS) therapy is a treatment option for CPAP intolerant obstructive sleep apnea. An increasing number of facilities offer UAS with varying levels of experience. Referring physicians may want to know whether the first set of patients have different outcomes from subsequent patients. We sought to quantify whether the surgical learning curve affects patient AHI and ESS outcomes. Methods: The ADHERE international multi-center registry is tracking UAS outcomes, including Apnea-Hypopnea Index (AHI), Epworth Sleepiness Scale (ESS) score, and surgical procedure time. Data were retrospectively reviewed from centers with at least 20 implants. The outcomes from each center's first ten implants were compared against the subsequent ten implants. Data are presented as mean (± standard deviation). Results: A total of 8 facilities had at least 20 implants for analysis, yielding 80 in the first ten implants group and 80 subjects in the subsequent ten implants group. Baseline age, gender, BMI, and pre-operative AHI and ESS were similar in both groups. UAS implantation time decreased significantly from 160 (±37) minutes (range: 72-287) for the first 10 implants to 145 (± 42) minutes (range: 77-329) for the subsequent 10 implants. (p<0.05) Conclusion: A learning curve effect is present in implantation time, yet similar improvements in post-titration AHI and ESS occurred over the first twenty implants. This finding may address referring physician concerns about initial patient outcomes when starting an UAS program. Support (If Any): ADHERE registry was sponsored by Inspire Medical Systems